Sailing - Evans, Jeremy (London : Heinemann, 1991)
A basic guide to the sport of sailing, introducing many kinds of boats and discussing what to do when a boat capsizes and other safety tips.
Includes index.
6.5
5-8.
Keywords: Sailing -- Juvenile literature; Sailing -- Safety measures -- Juvenile literature; Yachts and yachting -- Juvenile literature; Sailing; Sailing